2017
DOI: 10.18203/2320-1770.ijrcog20175826
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lifestyle and the frequency of polycystic ovary syndrome in Saudi female residing in Riyadh

Abstract: Background: Polycystic Ovary Disorder (PCOS) is perceived as the most widely recognized endocrinopathy in reproductive women. This study aimed to assess the relationship between the lifestyle and frequency of polycystic ovary syndrome in Saudi Arabia.Methods: This is a case-control study conducted on females at princess Nourah University (PNU), King Fahad Medical City (KFMC) and malls in Riyadh city, Saudi Arabia. The study included females in the reproductive age including 401 controls and 122 PCOS cases.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The congestion theory suggested that the lesion was the result of pressure, partial torsion, or other interruption in circulatory flow to the ovary. Finally, the dystrophy theory proposed that the abnormalities were caused by modifications or abnormalities in the nutrition of the ovary [1] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The congestion theory suggested that the lesion was the result of pressure, partial torsion, or other interruption in circulatory flow to the ovary. Finally, the dystrophy theory proposed that the abnormalities were caused by modifications or abnormalities in the nutrition of the ovary [1] .…”
Section: Resultsmentioning
confidence: 99%
“…This cross sectional study investigates the pattern of physical activity, daily dietary intake, the frequency of PCOS symptoms and other previously diagnosed diseases in normal women with and those having PCOS. It aimed to identify the possible unproven risk factors in relation to the disease as well as to estimate the level of general knowledge about PCOS in students [1] .…”
Section: Data Analysis and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The syndrome of polycystic ovary is one of the most widespread endocrinological diseases that involve women at childbearing age (Ibrahim et al, 2017). The exact cause behind PCOS is unfamiliar; however, studies submit that a complex feature appears at the time of puberty age (Roe andDokras, 2011).…”
Section: Introductionmentioning
confidence: 99%